APP, PSEN1, and PSEN2 Mutations in Asian Patients with Early-Onset Alzheimer Disease - Giau, Vo Van (Int J Mol Sci, 2019)
The number of patients with Alzheimer’s disease (AD) is rapidly increasing in Asia. Mutations in the amyloid protein precursor (APP), presenilin-1 (PSEN1), and presenilin-2 (PSEN2) genes can cause autosomal dominant forms of early-onset AD (EOAD). Although these genes have been extensively studied, variant classification remains a challenge, highlighting the need to colligate mutations across populations. In this study, we performed a genetic screening for mutations in the APP, PSEN1, and PSEN2 genes in 200 clinically diagnosed EOAD patients across four Asian countries, including Thailand, Malaysia, the Philippines, and Korea, between 2009 and 2018. Thirty-two (16%) patients presented pathogenic APP, PSEN1, or PSEN2 variants; eight (25%), 19 (59%), and five (16%) of the 32 patients presented APP, PSEN1, and PSEN2 variants, respectively. Among the 21 novel and known non-synonymous variants, five APP variants were found in Korean patients and one APP variant was identified in a Thai patient with EOAD. Nine, two, and one PSEN1 mutation was found in a Korean patient, Malaysian siblings, and a Thai patient, respectively. Unlike PSEN1 mutations, PSEN2 mutations were rare in patients with EOAD; only three variants were found in Korean patients with EOAD. Comparison of AD-causative point mutations in Asian countries; our findings explained only a small fraction of patients, leaving approximately 84% (p = 0.01) of autosomal dominant pedigrees genetically unexplained. We suggest that the use of high-throughput sequencing technologies for EOAD patients can potentially improve our understanding of the molecular mechanisms of AD.